Dissecting through Barriers: A Follow‐up Study on the Long‐Term Effects of Interprofessional Education in a Dissection Course with Healthcare Professional Students. Issue 1 (16th April 2018) - Zheng, Yu Hang (Eric); Palombella, Andrew; Salfi, Jenn; Wainman, Bruce
Abstract : Several studies have shown significant improvements in the attitudes and perceptions of healthcare professional students toward interprofessional education (IPE) immediately following intervention with IPE courses. However, there remains little evidence on the lasting effects of IPE courses and the long‐term influences of these IPE experiences are poorly documented. The purpose of this study is to assess the long‐term effects of an intensive, ten‐week interprofessional gross anatomy dissection course at McMaster University. Attitudes and perceptions of past participants towards interprofessional learning were evaluated, now that they have started working with other healthcare professionals outside of the IPE course setting. Thirty‐four past participants who have clinical experience working in interprofessional settings or are currently working in the healthcare field completed a follow‐up questionnaire consisting of a modified Readiness for Interprofessional Learning Scale (RIPLS) and open‐ended questions. Quantitative analysis revealed a significant decrease in their attitude towards teamwork and collaboration and respect for other health professions, but a significant improvement in their understanding of roles and responsibilities compared to their results immediately after the IPE intervention. Qualitative analysis of open‐ended questions revealed several themes such as developing interprofessional competencies, developing relationships, and remembering the strengths of the IPE dissection course. The results of this study indicate that the IPE experience in anatomy was highly valued by the students and that past participants maintain a clear understanding of their scope of practice, but the reality of clinical practice may have eroded gains made in the program. Anat Sci Educ. © 2018 American Association of Anatomists.